Prevalence of pruritus in the elderly in an outpatient dermatologic clinic: a monocentric pilot study - Sanja Javor; Luigi Priano; Antonio Anonide; Cesare Massone (Dermatology Reports, 2023)
Pruritus is a common dermatological condition; only few studies have investigated pruritus in old patients. To investigate the prevalence and features of pruritus in old patients which refer to the Dermatology Unit, Galliera Hospital in Genoa. We evaluated the demographic characteristics of all the patients attending for any skin condition the Outpatient Clinic at the Dermatology Unit, selecting those with pruritus and particularly focusing on patients aged more than 65 years.Pruritus was present in 36/262 patients (14%; M:F=20:16; mean age:59.55 years). Patients with pruritus older than 65 years were 20/262 (8%; M:F=14:6; mean age:74.6 years), that represented 14% out of the 140 patients aged ≥65 years. We found no statistically differences among patients aged≥65 years (20/36) and patients aged<65 years (16/36) concerning VAS pruritus. In 89% of patients itch was related to a dermatological condition, mainly psoriasis. Only extracutaneous diseases resulted more frequent in the patients aged>65. In none of these patients an anamnestic association between drug intake and the onset of pruritus was recorded. We confirm that pruritus is a common skin problem, that is equally frequent both sex, in young and old patients, that in almost all cases is related to an underlying skin condition (mainly psoriasis) and that is rarely anamnestic related to a new drug intake.